Activation of α7 nicotinic acetylcholine receptor decreases on-site mortality in crush syndrome through insulin signaling-Na/K-ATPase pathway - Bo-Shi eFan; En-Hui eZhang; En-Hui eZhang; Miao eWu; Jin-Min eGuo; Ding-Feng eSu; Liu eXia; Jian-Guang eYu (Frontiers Media S.A., 2016)
On-site mortality in crush syndrome remains high due to lack of effective drugs based on definite diagnosis. Anisodamine is widely used in China for treatment of shock, and activation of α7 nicotinic acetylcholine receptor (α7nAChR) mediates such antishock effect. The present work was designed to test whether activation of α7nAChR with anisodamine decreased mortality in crush syndrome shortly after decompression. Sprague-Dawley rats and C57BL/6 mice with crush syndrome were injected with anisodamine (20 mg/kg and 28 mg/kg respectively, i.p.) 30 min before decompression. Survival time, serum potassium, insulin, and glucose levels were observed shortly after decompression. Involvement of α7nAChR was verified with methyllycaconitine (selective α7nAChR antagonist) and PNU282987 (selective α7nAChR agonist), or in α7nAChR knockout mice. Effect of anisodamine was also appraised in C2C12 myotubes. Anisodamine reduced mortality and serum potassium and enhanced insulin sensitivity shortly after decompression in animals with crush syndrome, and PNU282987 exerted similar effects. Such effects were counteracted by methyllycaconitine or in α7nAChR knockout mice. Mortality and serum potassium in rats with hyperkalemia were also reduced by anisodamine. Phosphorylation of Na/K-ATPase was enhanced by anisodamine in C2C12 myotubes. Inhibition of tyrosine kinase on insulin receptor, phosphoinositide 3-kinase, mammalian target of rapamycin, signal transducer and activator of transcription 3, and Na/K-ATPase counteracted the effect of anisodamine on extracellular potassium. These findings demonstrated that activation of α7nAChR could decrease on-site mortality in crush syndrome, at least in part based on the decline of serum potassium through insulin signaling-Na/K-ATPase pathway.